The use of derivatives to hedge risk for plantation and property companies in Malaysia / Mohamad Azwan Md Isa, Norashikin Ismail and Nor Hadaliza Abd Rahman - Md Isa, Mohamad Azwan; Ismail, Norashikin; Abd Rahman, Nor Hadaliza (2017)
Global financial crisis during 2007-2009 had hit corporate sectors significantly. The corporations’ liquidity and profitability were affected so badly during the crisis that forced them to come up with hedging strategy to mitigate the risk. Hence, this study attempts to investigate the determinants corporations’ specific factors on the derivatives use among 71 Malaysian firms in the plantation and property sectors in hedging the risks. The study is divided into two sub-periods i.e. during financial crisis (2007-2009) and post financial crisis (2010-2012) using the public listed corporations at Bursa Malaysia and employing the Logistic Regression model. The findings revealed that growth opportunity of the corporations has significant impact on the derivatives use during the financial crisis whilst profitability and growth opportunity both contributed to the derivatives use post financial crisis. It is comfortably to say that the corporations with better growth and profitability tend to use the derivatives in hedging their risks. This is consistent with the risk management theory in order to mitigate underinvestment problem. Most importantly, this study indicates that the Malaysian firms in the two sectors are still risk averse as the derivatives use in hedging corporate risks is still at minimal level.